GEM research: Achievements and challenges (2014)
This article analyzes the content and evolution of research based on the Global Entrepreneurship Monitor (GEM) project. We conducted a rigorous search of articles published in journals within the Thomson Reuters' Social Sciences Citation Index® through an exploratory analysis focused on articles using GEM data. The main findings of this study reveal that the institutional approach is the most commonly used conceptual framework. Also, although there are still few academic publications using GEM data, the number of articles is increasing, as are opportunities for future research. © 2013 Springer Science+Business Media New York.